Teachers as curriculum leaders: what does this mean to school principals? - Bessong, Rebecca (Penerbit Universiti Kebangsaan Malaysia, 2024)
School leadership and accountability are usually the responsibilities of principals. Principals are expected to lead and manage in matters such as instructions, finance, staff development and community engagement. This solo leadership model is challenged by increasing pressure for high student achievement. The advent of teacher leadership presents teachers as valuable contributors in curriculum matters. Principals’ understanding of teachers as curriculum leaders (TCL) is important if teachers are to provide the much-needed assistance. The current research adopted a multiple-site case study design to explore principals’ understanding of the concept of TCL in schools. Eight participants were purposefully selected; open-ended, semi-structured interview guides were piloted prior to data collection. Observation of school meetings provided additional data. The data were thematically analysed and anchored on Grant’s model of teacher leadership. The findings reveal that, to school principals, TCL means teachers performing the roles of curriculum leaders and managers, decision makers, designers of learning programmes and materials, facilitators, assessors, lifelong learners, models, and pastoral caregivers. The findings further express the frustration of principals on the exclusion of teachers from curriculum decision making at the macro and meso levels. The findings are relevant in the advocacy of distributed leadership as they provide practical reasons for principals to create opportunities for teachers to lead in curriculum matters.